(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
The article examines the impact of technology on educational processes and teaching methods. Modern trends in the use of technologies such as adaptive learning, gamification, virtual and augmented reality, as well as artificial intelligence are considered. Examples of successful technology implementation in educational practice are given, problems and challenges are analyzed, including inequality in access, technical limitations and lack of digital competence. It is concluded that an integrated approach to technology implementation is important, and recommendations are given for educational institutions and developers. Directions for further research have been identified, including the long-term effects of digitalization of education.